Self-Esteem Research Guides School Achievement and Self-Esteem - Richardson, Robert B.; Rayder, Nicholas F. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Three self-esteem research guides, based on research data collected for the California Task Force to Promote Self Esteem, are presented. This research supported the belief that low self-esteem is directly related to low school achievement and school dropout. These assumptions are stated: (1) self-esteem can be measured; (2) a person's self-esteem can be changed; (3) change in a child's self-esteem can be directly influenced by a friend, a parent, a teacher, or another caring person; and (4) parents and teachers are critical players in developing a child's self-esteem. Each guide includes a chart that indicates the age and grade level appropriate for the research findings; a summary and explanation of the specific research finding; and suggestions to help teachers and parents translate the research findings into activities that can support self-esteem development. The first guide looks at the effects of self-confidence on school performance. The second guide discusses group counseling as a means to improve self-esteem and achievement levels for dropout prevention. The third guide looks at how a person's resources affect achievement. (LLL)
Teachers.
Parents.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Child Development; Elementary Secondary Education; Parent Role; Self Esteem; Teacher Role; Guides, General